2019
DOI: 10.1111/sms.13390
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a physical activity intervention in preschoolers: A cluster‐randomized controlled trial

Abstract: Several activity interventions in preschool settings exist, but little attention has been paid to effects on hemodynamic factors. The study aimed to assess the effectiveness of an exercise program on health-related outcomes including blood pressure (BP) and markers of vascular function in preschoolers, with focus on socioeconomic background. This study is a cluster-randomized controlled trial, with preschool as unit of randomization and children as unit of analysis. Preschools with 3-to 6-year-old children, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Although several studies show benefits of physical activity on the cardiometabolic risk profile of children [52], several recent meta-analyses have reported controversial results [49,53,54] and very little is known about preschoolers. In our systematic review, only five studies analyzed blood pressure among preschoolers [22,26,28,36,38]. In line with a Cochrane review in children and adolescents published in 2012 [54], our pooled analysis did not show significant reductions in systolic or diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although several studies show benefits of physical activity on the cardiometabolic risk profile of children [52], several recent meta-analyses have reported controversial results [49,53,54] and very little is known about preschoolers. In our systematic review, only five studies analyzed blood pressure among preschoolers [22,26,28,36,38]. In line with a Cochrane review in children and adolescents published in 2012 [54], our pooled analysis did not show significant reductions in systolic or diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 62%
“…Most studies included apparently healthy preschoolers, but two studies included overweight and/or obese children [28,32]. Participants enrolled in exercise cohorts were predominantly from the Germany (n = 4) [31,32,36,38], with studies from USA (n = 3) [20,21,35], Australia (n = 2) [29,37], Israel (n = 2) [27,34], Switzerland (n = 2) [24,33], China (n = 1) [28], Scotland (n = 1) [25], Spain (n = 2) [22,30], and Thailand (n = 1) [23]. All studies included boys and girls.…”
Section: Additional Analysismentioning
confidence: 99%
“…By contrast, Horner et al (22) found no change in aortic PWV in obese adolescents who participated in aerobic (treadmill training, 60-75% of VO 2peak ) or resistance (wholebody exercises) interventions for a period of three months. Moreover, Hacke et al (59) implemented preschool exercise lessons (45 min, two times per week for six months) but was unable to detect any improvement in aortic PWV in the intervention group compared to controls.…”
Section: Vascular Functionmentioning
confidence: 97%
“…As such, we can conclude that exercise interventions with at least moderate levels of intensity can reduce vascular stiffness among pediatric populations at risk. Horner et al (22) and Hacke et al (59) reported no reductions in body mass index in response to these interventions; improvement in vascular function might be linked to a change in anthropometric parameters. It is also possible that the intensity of their intervention was too low to promote measurable changes in vascular function.…”
Section: Vascular Functionmentioning
confidence: 97%
“…lead to a decrease in motor activity. This is noted in the works of Komkov a high interest in optimizing motor activity and making programs, taking into account social factors that characterize the educational process in various countries of the world [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%